Gender Disparities in India: Causes, Impacts, and Measures - Dr. Nijra Brahma, (Indian Journal of Social Science and Literature (IJSSL), 2024)
The gender gap that still exists in Indian society has touched the various spheres of life such as education, employment opportunities, income, health, economic issues, social and cultural issues, etc. Discrimination towards women starts even before her birth in the form of female foeticide and after her birth in the form of female infanticide has been in practice. Gender inequality restricts women’s access to opportunities and resources. In this paper, we have tried to highlight the causes and consequences of gender inequality in India and put forward measures to reduce this inequality.